Meningkatkan Hasil Belajar Siswa Kelas 1 Tema 7 Materi Penjumlahan dan Pengurangan Menggunakan Pendekatan Pembelajaran Matematik Realistik di SDN Kamal 3 - Vita Marwati; Agung Setyawan (Jurnal Pendidikan Indonesia, 2022)
The ability to count in early or low grades has an important role as the basis for achieving student learning activities in mathematics. Unconsciously, they often use mathematical operations in everyday life. The learning approach is very important to be applied by a teacher so that students can understand the material quickly and can improve student learning outcomes. This research was conducted to improve student learning outcomes by applying a realistic mathematics learning approach to the addition and subtraction material for grade 1 at Kamal State Elementary School 3. The research method used was Classroom Action Research. The researcher used a classroom action research design developed by Kemmis and Mc Taggart. The study used the subjects of all grade 1 students at SDN Kamal 3 Bangkalan. The number of grade 1 students is 25 children, consisting of 12 female students and 13 male students. Researchers used data collection techniques by means of interviews, tests and documentation. The assessment instruments used were interview and test instruments, as well as data analysis techniques with qualitative descriptive. The results of the research are explained in each cycle, there are 4 stages in each cycle consisting of planning, implementation, observation, and reflection. In the first cycle, the students' average score was not in line with the researcher's expectations, which was 63.6 where the score did not meet the KKM requirements. It was different after the action was taken, in the second cycle the average value was 77, 6, where the value was in accordance with the KKM requirements. Based on research, the acquisition of grade 1 students at SDN Kamal 3 in addition and subtraction material using a realistic mathematical (PMR) can improve student learning outcomes. Through the media of candy and story questions related to life